2021
DOI: 10.26686/wgtn.14331389.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of cancer stem cells and the renin-angiotensin system in colon adenocarcinoma

Abstract: Colorectal cancer (CRC) is the third most common cancer and the second highest cause of cancer deaths globally. More than 70% of CRC-related deaths are due to metastasis to the liver. The cancer stem cell (CSC) concept hypothesises that CSCs drive tumour growth, chemoresistance, recurrence and metastasis. Markers such as CD133, LGR5 and EpCAM, have been used to identify and isolate CSCs in CRC. However, these markers are often expressed by cells with no stem cell properties and are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 163 publications
(280 reference statements)
0
4
0
Order By: Relevance
“…However, there are currently no specific antibodies against AT 1 R. One laboratory has tested six commonly-cited anti-AT 1 R antibodies using various knock-out models and cells known to be negative for AT 1 R, and found that these antibodies all detected bands at around 43 kDa (the predicted size of AT 1 R), and produced a variety of staining intensities and localizations by IHC staining not specific for AT 1 R [48]. AT 1 R was not detected in our CA tissues or primary cell lines when analyzed by mass spectrometry, possibly because integral membrane proteins can be difficult to isolate during sample preparation [38]. Therefore, despite being a potential target for RAS modulation in the treatment of cancer, determination of AT 1 R protein expression and localization was not performed in this study.…”
Section: Plos Onementioning
confidence: 82%
See 3 more Smart Citations
“…However, there are currently no specific antibodies against AT 1 R. One laboratory has tested six commonly-cited anti-AT 1 R antibodies using various knock-out models and cells known to be negative for AT 1 R, and found that these antibodies all detected bands at around 43 kDa (the predicted size of AT 1 R), and produced a variety of staining intensities and localizations by IHC staining not specific for AT 1 R [48]. AT 1 R was not detected in our CA tissues or primary cell lines when analyzed by mass spectrometry, possibly because integral membrane proteins can be difficult to isolate during sample preparation [38]. Therefore, despite being a potential target for RAS modulation in the treatment of cancer, determination of AT 1 R protein expression and localization was not performed in this study.…”
Section: Plos Onementioning
confidence: 82%
“…The downstream effects of AT 2 R and Mas receptor agonism counteract those of AT 1 R. Adapted with permission from Munro et al Integr Cancer Sci Therap. [10] and from [38]…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations